Dispensing errors in hospital pharmacies in Yemen: an exploratory study - Al-Worafi, Yaser Mohammed; Elkalmi, Ramadan Mohamed Mahmod; Ming, Long Chiau; Othman, Gamil; Halboup, Abdulsalam; Battah, Mohammed; Dhabali, Abdullah; Jaber, Ammar; Al-Shami, Abdulkareem Mohammed; Alakhali, Khaled; Alseragi, Wafa; Alshakhshir, Sami; et al. (University of Tripoli, Libya, 2021)
Aims. This study aimed to describe the dispensing errors that occurred during the dispensing process in selected hospital pharmacies in Sana'a, Yemen, and to describe their types and causes. Methodology. A prospective study was carried out in selected hospital pharmacies in Yemen over 40 days using a validated tool. Results. A total of 9000 dispensed prescriptions were evaluated for the dispensing errors, and 2.13% dispensing errors were identified. Wrong dosage form (134/192), incorrect strength (24/192), wrong drug (18/192), incorrect quantity, wrong instructions written and drug available in the pharmacy but not given (6/192) and dispensing expired drugs (3/192) were the dispensing errors reported in this study. Poor handwriting, similar drug names, similar drug packaging, fatigue, heavy work, workforce issues, and poor communication were the most commonly reported causes of dispensing errors. Conclusion. There is a wide variation in the rates of prevalence of medication errors observed during this prospective study. Dispensing errors were the most common. This variation may be attributed to the nature and heterogeneity of the prescription’s sources. Study results indicate that medication errors imposed an extraordinary challenge to the healthcare system in Yemen and post significant potential harm to the patient in light of the current economic, social and security conditions. Well-designed nationwide future studies aimed at investigating the causes of medication errors to guide the design of interventions aimed at reducing their burden on the national healthcare system is highly recommended.